Analysis of Pile Foundation Bearing Capacity based on SPT Data on the Pillar of the T. Nyak Makam Canal Bridge, Santan, Banda Aceh - Yuslinda, Yuslinda; Rani, Cut Meutia (Fakultas Teknik Universitas Tanjungpura, 2025)
The T. Nyak Makam Canal Bridge in Santan, Banda Aceh, serves as a vital transportation link, spanning 135 meters in length and 24,6 meters in width. This study presents a comprehensive analysis of the pile foundation bearing capacity, utilizing Standard Penetration Test (SPT) data to evaluate the middle pillar